Wireless resource virtualization: opportunities, challenges, and solutions. Issue 16 (29th July 2016) - Kalil, M.; Youssef, M.; Shami, A.; Al‐Dweik, A.; Ali, S.
Abstract: Wireless resource virtualization (WRV) is currently emerging as a key technology to overcome the major challenges facing the mobile network operators (MNOs) such as reducing the capital, minimizing the operating expenses, improving the quality of service, and satisfying the growing demand for mobile services. Achieving such conflicting objectives simultaneously requires a highly efficient utilization of the available resources including the network infrastructure and the reserved spectrum. In this paper, the most dominant WRV frameworks are discussed where different levels of network infrastructure and spectrum resources are shared between multiple MNOs. Moreover, we summarize the major benefits and most pressing business challenges of deploying WRV. We further highlight the technical challenges and requirements for abstraction and sharing of spectrum resources in next generation networks. In addition, we provide guidelines for implementing comprehensive solutions that are able to abstract and share the spectrum resources in next generation network. The paper also presents an efficient algorithm for base station virtualization in long‐term evolution (LTE) networks to share the wireless resources between MNOs who apply different scheduling polices. The proposed algorithm maintains a high‐level of isolation and offers throughput performance gain. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Wireless resource virtualization (WRV) is emerging as a key technology to reduce cost and increase the total network capacity by sharing wireless resources between multiple mobile operators. In this paper, we present the concepts, highlight the benefits, and discuss the technical challenges and requirements for abstraction and sharing of WRV in next generation networks. Furthermore, an efficient WRV approach for long‐term evolution base stations is proposed and evaluated.